Mapping Learning Outcomes and Teaching Materials for Islamic Education in Aqidah: Content and Pedagogical Continuity in the Independent Curriculum - Rahmawati, Marshanda Rosy; Fakhruddin, Agus; Romli, Usup (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2025)
Aqidah, as an essential part of the Islamic Religious Education (PAI) and Character Development element in the Independent Curriculum, should have continuous learning outcomes and teaching materials from elementary to secondary school levels. Ideally, the Independent Curriculum should provide significant space for developing religious and moral values in education while promoting tolerance toward diverse beliefs and cultures to create an inclusive environment. This contributes to the formation of strong character and a spirit of unity in diversity. To obtain an overview of the continuity of learning outcomes and teaching materials for PAI and Character Development in the aqidah element, a mapping based on the characteristics of aqidah itself is necessary. This study employs a qualitative approach using content analysis methods. The data sources consist of documents from the Independent Curriculum for the PAI and Character Development subject, analyzed through document studies. The findings indicate that the Ilahiyyah dimension is present in all curriculum phases. In contrast, the Nubuwwat dimension is explicitly found in phases A, B, and D. The Ruhaniyyah dimension is only found in phases A and D. In contrast, the Sam’iyyat dimension appears in phases A, C, and D. The teaching materials also show a gradual progression, from introducing basic concepts in elementary school to critical analysis in high school. These findings suggest that while there is continuity in the curriculum, the distribution of materials across phases still needs evaluation to ensure better integration in aqidah learning.